Perbandingan Luaran Klinis Favipiravir dan Remdesivir pada Pasien Covid-19 Derajat Sedang di RS Akademik UGM Yogyakarta - Hadiatussalamah Hadiatussalamah; Tri Murti Andayani; Ika Puspita Sari (Faculty of Pharmacy, Universitas Gadjah Mada, 2023)
Research on effective antivirals for COVID-19 is still ongoing. Favipiravir and remdesivir are antivirals that have been recommended in Indonesia. This study aimed to compare the clinical outcomes of favipiravir and remdesivir in moderate COVID-19 patients. This research is a retrospective cohort study conducted at the UGM Academic Hospital Yogyakarta using electronic medical records of moderate COVID-19 who were hospitalized from June 2021 to March 2022. Each therapy group consisted of 88 subjects. Clinical outcomes in the form of improved and not-improved conditions were assessed using a 7-point ordinal scale of progressivity and recovery of COVID-19 from WHO. Chi-square analysis and multiple logistic regression were performed to determine the relationship between the research variables. The highest percentage of research subjects were aged 18 – 59 years (70,5%), male (53,4%), and not obese (64,2%). The most common comorbidities were diabetes mellitus (33%) and hypertension (30%). The favipiravir group had a better clinical outcome than remdesivir. The proportion of patients improving in the favipiravir group was 50,0% and 35,3% in the remdesivir group (p-value=0,048). There was no significant difference in the number of adverse events between both study groups (p-value > 0,05). The most common adverse drug events were nausea (35,2%), vomiting (14,2%), and heartburn (11,4%).